2022
DOI: 10.3390/ijms23031494
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Gut Microbiota and Osteoarthritis: Does the Disease Begin in the Gut?

Abstract: Some say that all diseases begin in the gut. Interestingly, this concept is actually quite old, since it is attributed to the Ancient Greek physician Hippocrates, who proposed the hypothesis nearly 2500 years ago. The continuous breakthroughs in modern medicine have transformed our classic understanding of the gastrointestinal tract (GIT) and human health. Although the gut microbiota (GMB) has proven to be a core component of human health under standard metabolic conditions, there is now also a strong link con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 179 publications
(232 reference statements)
0
12
0
3
Order By: Relevance
“…Unravelling the emerging factors influencing susceptibility/resistance to inflammation (genetic background, microbiota composition, metabolomic profiles) will be crucial to provide precise nutritional and lifestyle recommendations for specific groups of OA sufferers (e.g., personalized approaches based on inflammatory epigenetic signatures) [ 249 , 250 ]. In this context, the gut is a new and intriguing target for OA, as gut dysbiosis is one of the factors contributing to the pathophysiology of OA [ 251 , 252 ], where PPs have important roles. Lan et al showed that the daily intragastric administration of quercetin in the MIA-induced OA model, from day 1 to day 28, partially reversed intestinal flora disorder [ 253 ].…”
Section: From Basic Research To Translational Applications Of Ppsmentioning
confidence: 99%
“…Unravelling the emerging factors influencing susceptibility/resistance to inflammation (genetic background, microbiota composition, metabolomic profiles) will be crucial to provide precise nutritional and lifestyle recommendations for specific groups of OA sufferers (e.g., personalized approaches based on inflammatory epigenetic signatures) [ 249 , 250 ]. In this context, the gut is a new and intriguing target for OA, as gut dysbiosis is one of the factors contributing to the pathophysiology of OA [ 251 , 252 ], where PPs have important roles. Lan et al showed that the daily intragastric administration of quercetin in the MIA-induced OA model, from day 1 to day 28, partially reversed intestinal flora disorder [ 253 ].…”
Section: From Basic Research To Translational Applications Of Ppsmentioning
confidence: 99%
“…In the future, diet, fecal transplantation, and future therapies targeting the microbiota are estimated to be approached in all diagnostic and therapeutic protocols. Consequently, diet control (especially foods with low gluten content and enriched in indigestible B) could open new scientific horizons in the occurrence and monitoring of OA pathology [ 6 , 31 , 32 , 33 , 34 ]. More and more studies have shown that the reduced buffering capacity of saliva is related to periodontal disease and caries.…”
Section: Oral Microbiome In Mouth and Systemic Diseasesmentioning
confidence: 99%
“…The gut is inhabited by trillions of bacteria and other microorganisms which are increasingly recognized as significant contributors to human health. Disturbances to the gut microbiota (i.e., dysbiosis) have been associated with a wide variety of age-related health conditions including bowel, pulmonary, neurologic, skeletal, metabolic, and autoimmune diseases [87][88][89]. In addition, shifts in the gut microbiota have been linked mechanistically to physiological hallmarks of aging, including chronic inflammation [90], genomic instability [91], mitochondrial dysfunction [92], reduced proteostasis [93], and epigenomic modifications [91].…”
Section: Gut Microbiomementioning
confidence: 99%